THE EFFECT OF SYSTEM AND OXYGEN PARTIAL PRESSURE ON SINGLE COAL PARTICLE HETROGENOUS IGNITION TEMPERATURE UNDER CONDITIONS OF NEGLIGIBLE CONVECTION; EXPERIMENTAL OBSERVATION - Katalambula, H. (Tanzania Journal of Engineering and Technology, 2018)
Abstract